Competence-Based Human Resource Development: A Literature Study in the Era of Information Technology and Digitalization - Kamal Alamsyah; Avid Leonardo Sari; Pri Utami; Fadjar Adzani; Abdul Haris (Global Writing Academica Researching & Publishing, 2023)
The research was conducted to explore competency-based human resource development. Utilizing secondary data, the strategy was qualitative with a literature review approach. The study result stresses the significance of competency-based human resources (HR) development for the success of organizations or businesses in the rapidly expanding digital and technology era. The impact of technology and digitalization on competency-based HR development, the difficulties organizations face in creating HR in the digital era, successful HR development strategies, the competencies required by HR in the digital era, and the role of HR in the success of organizations in the digital era have all been covered in this paper.